Potential application of light element stable isotope ratio in crude fiber for geographical origin verification of raw and cooked kabocha pumpkin (Cucurbita maxima) - Yoshida, Mitsuru; Tabata, Ayane; Niino, Takumi; Chiku, Kazuhiro; Nakashita, Rumiko; Suzuki, Yaeko (Food Chemistry, 2022)
•δ13C and δ18O were used for geographical origin discrimination of kabocha pumpkin.•Kabocha of Hokkaido, Japan was discriminated from those of Mexico and New Zealand.•δ13C and the δ18O of flesh were affected by seasonings after cooking or processing.•Effects of seasonings on δ13C and δ18O were eliminated by extracting crude fiber.•δ13C and δ18O of crude fiber can be used for verification even after cooking. In this study, we investigated the possibility of the geographical origin discrimination between Japanese and Mexican kabocha pumpkin using δ13C and δ18O in lyophilized raw flesh. Kabocha harvested in Hokkaido, the major kabocha production area in Japan, could be discriminated against not only that grown in Mexico but also that in New Zealand. However, seasoning after cooking or processing affected the δ13C and the δ18O values. Crude fiber extraction eliminated the effect of seasonings and enabled the adoption of the δ13C and δ18O values in crude fiber for the geographical origin verification of kabocha even after cooking and processing. The usage of δ13C and the δ18O in crude fiber would extend the application possibilities of stable isotope analysis in the geographical origin determination of various cooked and processed vegetables and fruits as well as raw materials.